Features of weather around Syowa Station in the ACR period, 1987-1991 - Susumu Kaneto (National Institute of Polar Research, 1997)
Meteorological data obtained at Syowa Station and Asuka Station during the Antarctic Climate Research (ACR) period (1987-1991) are analyzed compared with normal values and Mizuho Station data. At Syowa, the first half of the period was characterized by weak wind and less snow accumulation, and sea ice around Syowa blew offshore during the summer season frequently. In the lower stratosphere, the largest sudden warming was observed over Syowa in the spring of 1988,but the polar vortex did not decay as one would expect. At Asuka, 5 years of data were obtained. It was revealed that the yearly mean wind speed is largest at inland stations.